Reproductive efficacy of a modified-live porcine reproductive and respiratory syndrome vaccine against Korean PRRSV-2 challenge in sows - Suh, Jeongmin; Kim, Tae-Eun; Ham, Sehyeong; Na, Hyejin; Kang, Ikjae; Cha, Sang-Ho; Cho, Sun Hee; Chae, Chanhee (Frontiers in Veterinary Science, 2026)
BackgroundEvaluation of the reproductive efficacy of a modified-live vaccine (MLV) based on porcine reproductive and respiratory syndrome virus-2 (PRRSV-2).ObjectiveThe objective of this study was to evaluate the efficacy of a MLV based on porcine PRRSV-2 against a heterologous Korean PRRSV-2 lineage 1 strain challenge in pregnant sows.AnimalsTwelve pregnant sows from PRRSV-free farms were randomly assigned to three groups (four sows per group).MethodsSows in the vaccinated-challenged group received a 2.0 mL intramuscular dose of PRRSV-2 MLV and were subsequently challenged intranasally with a heterologous PRRSV-2 strain.ResultsVaccinated-challenged sows improved reproductive performance, including a higher number of live-born piglets and fewer stillbirths compared with unvaccinated-challenged sows. Viral genomic loads were lower in vaccinated-challenged sows and their offspring as well. Vaccinated-challenged sows also elicited a significantly higher frequency of PRRSV-2 specific interferon-γ secreting cells.DiscussionThese findings demonstrated that the PRRSV-2 MLV administered to pregnant sows provide protection against heterologous challenge through clinical, virological, and immunological evaluation.